Let a b = 1 and define
P = a + 1 a + b + 1 b and Q = a + 1 1 + b + 1 1 .
What can we say about P and Q ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
p=a/(a+1)+b/(b+1) =(b/b) a/(a+1)+(a/a) b/(b+1) because a/a=b/b=1 =ab/(ab+b)+ab/(ab+a) =1/(1+b)+1/(1+a) because (ab=1) =Q
take L.C.M. of P and Q and compare them.they will be equal.
but given question is different
Log in to reply
Qi Huan Tan has merely substituted ab for 1 in the expression for Q
okay i understood
asume that they are equal :p
P = a + 1 a + 1 − 1 + b + 1 b + 1 − 1
P = 2 − Q
P > Q
Where is the mistake?
Log in to reply
Mmmm but if p=1 q=1 then
p=2-q
1=2-1
You should take into account that ab=1 (Sorry for my bad english)
what if a=-1 ?
you have given the solution for a different question!!!!!!!!!
Let ab=1. Define ...it should be Let a and b = 1, Define to make the answer P=Q
Beyond the quick ways to show that P and Q are equal, you can show that both P and Q are 1 making the equality is trivial.
P = a + 1 a + b + 1 b = a + 1 a + 1 / a + 1 1 / a = a + 1 a + a + 1 1 = a + 1 a + 1 = 1
Q = a + 1 1 + b + 1 1 = a + 1 1 + ( 1 / a ) + 1 1 = a + 1 1 + a + 1 a = a + 1 a + 1 = 1
P= (1\ 1+1/a )+1/ (1+1/b). Now 1+1/a may be greater than or equal to less than a+1. similarly 1+1/b may be greater than or equal to or less than 1+b. Hence the answer is wrong
Write a comment or ask a question...
Log in to reply
I don't follow your explanation. I've double checked my calculations and can't see any mistakes. Could you point out a step in my first calculation that you think is incorrect?
There is no presumption that ab=1 in this problem Write a comment or ask a question...
Log in to reply
The first words at the top of the problem are "Let ab = 1"...
Log in to reply
you are right as there is the misunderstanding of the word "let" and "if"
What about when a=0 and b=0 then P=0 and Q=2 . This also shows the given answer P= Q is wrong for any set of values of a and b. Write a comment or ask a question...
Log in to reply
Since ab = 1 we know that a and b can't be 0.
b=1/a ; substitute b =1/a in P and Q . We will get same equation.
ab=1 or a=1/b; or a+1= (1+b)/b; or b/(b+1) = 1/(a+1);
Therefore , P = a/(a+1) + 1/(a+1); (Substituting second term) or P = 1 Similarly from ab = 1 we can get 1/(b+1) = a/(1+a);
So Q = 1/(a+1) + a / (1+a) (Substituting the second term) Simplifying Q=1 Therefore P=Q
We just need to substitute the variables to solve the question.
a b = 1
P = a + 1 a + b + 1 b
Q = a + 1 1 + b + 1 1
Expanding P :
P = a + 1 a + b + 1 b
Substituting 1 = a b :
P = a + a b a + b + a b b
P = a ( 1 + b ) a + b ( 1 + a ) b
P = 1 + b 1 + 1 + a 1 = Q
Therefore, P = Q ( P and Q are same).
Thus, the answer is: P = Q
Taking, Q=(b/b) (1/a+1)+(a/a)(1/b+1), using the fact that ab=1 we find that P=Q. I first liked the problem and then reshared it but as i researched the problem i find that it's cursed with the fact that it can easily be solved by putting values of a and b. So i un- shared it then.
just change it to... PROVE that P=Q
by solving using LCM we can get the answer easily.
take P/Q=(a(b+1)+b(a+1))/b+1+a+1 =ab+a+ab+b/a+b+2 =a+b++2ab/a+b+2 =a+b+2(1)/a+b+2 =a+b+2/a+b+2 =1 so P/Q=1 =>P=Q
P and Q are equal because they have the same product.
P=a/(a+1) +b/(b+1) =a(b+1)+b(a+1)/(a+1)(b+1) =ab+a+ab+b/ab+a+b+1 =1+a+1+b/1+a+b+1 =a+b+2/a+b+2 =1 now, Q=1/(a+1)+1/(b+1) =b+1+a+1/(a+1)(b+1) =a+b+2/ab+a+b+1 =a+b+2/a+b+1+1 =a+b+2/a+b+2 =1 so, P=Q
P= (1)/ (1)+1 + (1)/(1)+1 Q= 1/(1)+1 + 1/(1)+1
For P, p=a/(a+1) + b/(b+1) , p=a(b+1)+b(a+1)/(a+1)(b+1) , p=ab+a+ab+b/(a+1)(b+1) , p=ab+ab+a+b/(a+1)(b+1) , p=2ab+a+b/(a+1)(b+1) , since , ab =1 put the value of ab =1 in given equation ... p=2(1)+a+b/(a+1)(b+1),
then Q, Q= 1/(a+1) + 1(b+1) , Q=b+1+a+1/(a+1)(b+1) , Q=2+a+b/(a+1)(b+1) , so the answer is .. P=Q
just assuming the value a and b....
The most simple way is to substitute any values of a and b in both equations...in this case you get same answer of both...
you should take care that your answer doesn't come infinity
Since ab =1 therefore value of a & b are 1( 1X1 for a & b +1) Substituting these vvalue for expressions P & Q gives values as 1 therefore P = Q nswer.
K.K.GARG.india
p=q= (a+b+2)/(a+1)(b+1)
after solve p=\frac { 2+a+b }{ (a+1)(b+1) }
Q=\frac { 2+a+b }{ (a+1)(b+1) } so P=Q
just multiply the first component of expression of P by "b" in numerator and denominator and the second component of P by "a" in numerator and denominator and you will get an expression which is equal to Q
Problem Loading...
Note Loading...
Set Loading...
P = a + a b a + b + a b b = 1 + b 1 + 1 + a 1 = Q